Lead failure in transvenous implantable cardioverter defibrillator: a new opportunity for an effective management - Pignalberi, Carlo (Clin Case Rep, 2018)
In case of transvenous defibrillator lead failure, a subcutaneous defibrillator may be implanted and the lead may be abandoned in order to avoid particular risk situations. For patients who require pacing and with an operational atrial lead, the transvenous ICD may be also maintained to ensure antibradycardia support.